Evaluation of the detection of diarrhoea-associated RNA viruses in immunocompromised children in Iran - Shokouh Yasaie; Seyed Dawood Mousavi Nasab; Saeed Shams; Atousa Ferdousi; Hooman Kaghazian (Infection Prevention in Practice, 2024)
Summary: Background: Gastroenteritis accounts for about 10% of the deaths among children, especially in immunocompromised children. Few studies on the prevalence of gastrointestinal infections caused by RNA viruses have been done in Iran. The aim of the study was to evaluate the detection of RNA viruses causing diarrhoea using a multiplex PCR. Methods: Stool samples were collected from 130 paediatric patients with diarrhoea who had acute lymphocytic leukaemia, non-Hodgkin lymphoma, and retinoblastoma. After RNA extraction and synthesis of cDNA, multiplex PCR was done to evaluate the presence of rotavirus, norovirus, astrovirus, and enterovirus. Results: There were 9 (6.9%), 7 (5.4%), 3 (2.3%), and 6 (4.6%) cases of rotavirus, norovirus, astrovirus, and enterovirus detected, respectively. One case of co-infection with astrovirus and norovirus was observed. Conclusions: This is the first report from Iran which identified the presence of common RNA viruses causing diarrhoea in immunocompromised children. Increased awareness of these viruses will enable healthcare professionals to improve strategies and policies to control spread and infection caused by these viruses.